Toxicology, survival and health hazards of combustion products - Purser, David A.; Maynard, Robert L.; Wakefield, James C. (James Christopher) (Issues in toxicology ;, 2015)
Fires are a common source of exposure to smoke and a range of toxicologically active chemicals. Providing a complete overview of the subject, this book provides comprehensive and detailed information on combustion processes, estimation of rate of production of combustion products, dispersion of these products and their effects on health. Beginning with a chapter discussing the chemistry of combustion and detailing the mechanisms of burning, how different materials ignite and the nature of combustion products, the book goes on to examine specific combustion products in detail, the toxicity and carcinogenicity of the products, their dispersion and methods of monitoring. With diverse coverage edited and authored by recognised experts in the field, this book will provide an essential text for those working in toxicology, combustion science, public health and environmental research.